2005
DOI: 10.1111/j.1365-2486.2005.00941.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of agricultural change on abundance, fitness components and distribution of two arctic‐nesting goose populations

Abstract: Intensification of agriculture since the 1950s has enhanced the availability, competitive ability, crude protein content, digestibility and extended growing seasons of forage grasses. Spilled cereal grain also provides a rich food source in autumn and in winter. Long-distance migratory herbivorous geese have rapidly exploited these feeding opportunities and most species have shown expansions in range and population size in the last 50 years. Results of long-term studies are presented from two Arctic-breeding p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(174 citation statements)
references
References 31 publications
3
162
1
3
Order By: Relevance
“…Other authors have also found that geese preferentially forage in larger fields (e.g. Gill 1996;McKay et al 2006) as well as in more intensively used farmland (Fox et al 2005). However, we are not aware of any earlier studies showing that crop diversity negatively affected foraging site choice by geese during migration.…”
Section: Spatial Pattern In Flock Sizecontrasting
confidence: 44%
See 2 more Smart Citations
“…Other authors have also found that geese preferentially forage in larger fields (e.g. Gill 1996;McKay et al 2006) as well as in more intensively used farmland (Fox et al 2005). However, we are not aware of any earlier studies showing that crop diversity negatively affected foraging site choice by geese during migration.…”
Section: Spatial Pattern In Flock Sizecontrasting
confidence: 44%
“…However, we are not aware of any earlier studies showing that crop diversity negatively affected foraging site choice by geese during migration. Thus, geese are one of the few examples of species which may benefit from intensive agriculture (Van Eerden et al 1996;Fox et al 2005). However, site choice by geese is inevitably different from that of the declining populations of farmland birds which are mostly territorial during the breeding season.…”
Section: Spatial Pattern In Flock Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The relative ease with which pinkfooted geese have been able to adapt to the loss of the Filsø feeding site points to substantial cognitive plasticity that likely relates to its habitat use (Madsen 2001). The switch to an agricultural diet characteristic of both this population (Fox et al 2005) and other species of geese (Rosin et al 2012) opened the door to an almost inexhaustible food resource in the Danish landscape, and the availability of staging sites during the autumn migration may therefore depend more strongly on the relative proximity of secure roosting areas rather than specific food resources. As a consequence, philopatric waterfowl species exploiting cultivated areas might be much less susceptible to changes in staging areas than species targeting specific food sources much less available in a modern landscape (Clausen et al 2012;Fox et al 2011;Wang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The population currently totals 76,000-81,000 birds (2013)(2014), and has been steadily increasing over the last decades . During the non-breeding period, pink-footed geese forage most commonly on energy-rich agricultural plant matter such as waste grain on cereal stubble fields, newly sown winter cereals, pastures, and newly sown spring cereal grain fields (Fox et al 2005). Like other goose species, they prefer open areas that allow sufficient look-out for potential dangers (Madsen 1985a;Rosin et al 2012).…”
Section: Study Populationmentioning
confidence: 99%